RELASI KEMISKINAN PADA PRAKTEK PERDAGANGAN PEREMPUAN KELAS BAWAH DALAM DUNIA PROSTITUSI : Studi Kasus pada Pekerja Seks Komersial di Desa Bongas Kecamatan Bongan Kabupaten Indramayu - Eri Susanto; Nike Vonika; Ahmad Yaneri (Politeknik Kesejahteraan Sosial Bandung, 2023)
Human trafficking can be categorized as transnational organized crime. The problem of human trafficking is very complex. Efforts to prevent and overcome trafficking victims must be carried out in an integrated manner. This study aims to explore: 1) the processes and ways in which women are entangled in the practice of covert prostitution 2) social networks those are formed in the practice of covert prostitution, and 3) the factors that encourage women to become entangled in the practice of covert prostitution. The research uses a qualitative method. Research data sources are the Bongas Village Government, women are entangled in the practice of covert prostitution, and activist at the Yayasan Bunga Bangsa. The locus of this study is located at Bongas Village, Sub District of Bongas, Indramayu District, West Java Province. The selection of this locus is because there are women who are trapped in covert prostitution and Bongas Kusuma Foundation engaged in community empowerment and development. The results of the study show as follows: 1) the way to ensnare women into covert prostitutes is to provide high income offers, 2) the social network formed in the case of trafficking in women who were used as prostitutes in the form of partial social networks and social networks of interests, and 3) The background factors that cause women to become victims of trafficking are factor of economic poverty, factor of limited employment opportunities, factor of the low level of education, factor of family problems, and factor of early marriage that have an impact on divorce